Can a Rule-Based Monetary Policy Framework Work in a Developing Country? : The Case of Yemen - Elekdag, Selim (IMF Working Papers; Working Paper ;, 2007)
Monetary policy in Yemen is largely rudimentary and ad hoc in nature. The Central Bank of Yemen's (CBY) approach has been based on discretionary targeting of broad money without any clear target to anchor inflation expectations. This paper argues in favor of a new formal monetary policy framework for Yemen emphasizing a proactive and rule-based approach with a greater direct focus on price stability in the context of a flexible management of the exchange rate. Although, as in many developing countries, institutional capacity is a concern, adopting a more formal framework could impel the kind of changes that are required to strengthen the ability of the CBY in achieving low and stable rates of inflation over the medium term.